The effects of inter-cropping maize with beans on maize diseases infestation (Makerere University Journal of Agricultural & Environmental Sciences, 2002)
A study was carried out to assess the effects of inter-cropping maize with beans on maize diseases infestation Eight diseases were recorded to affect maize with maize streak virus, northern leaf blight (Exserohilum turcicum), gray leaf spot (Cercospora zeae-maydis), and Sternocarpella macrospora leaf blight (Sternocarpella macrospora), being most prevalent. Disease incidence ranged between 0% for sorghum downy mildew (Peronosclerospora sorghi) to 80% for gray leaf spot. Gray leaf spot was the most common and was in some instances the most severe disease and attacked all varieties irrespective of the cropping system. Despite the high severity scores however, gray leaf spot disease did not affect maize yield. Other diseases also developed irrespective of whether the maize was sole or inter-cropped thus, resulting in no significant difference in disease reaction between mono or intercropped maize. In this particular study, intercropping maize with beans was not found to reduce maize streak virus disease incidence and severity as reported in earlier studies. These variable findings underscore the need for further work on disease incidence and development under mixed cropping systems.
Keywords: Cropping System; Gray leaf spot; yield; Zea mays